Clinical types and possible etiologies of neonatal seizures: A hospital based study - AL-Naddawi, Mahjoob N.; Hameed, Numan N.; Kadum, Meisloon J. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Seizures in the neonatal period are common. They can present as focal clonic, focal tonic, myoclonic, generalized tonic and subtle seizures. They can be caused by a variety ofconditions, ranging from benign self-limited illnesses to severe life-threatening disorders.Patients and methods: A prospective study included 75 neonates with seizures in the first 28 days of life were admitted to neonatal care unit in Children Welfare Teaching Hospital from January 15th 2009 to August 15th 2009. A Full history was obtained and patients were examined by a specialist in the neonatal care unit and the researcher. Laboratory investigations and neuroimaging studies were done for all patients.Results: Out of 75 neonates, (55%) were males and (45%) were females with a male: female ratio of 1.2:1, (76%) of them was delivered at term. The onset of seizures was reported in the first 72 hours of life in (42.6%) of neonates. The most common type of seizure was tonic type (48%) followed by subtle type (24%), focal clonic 16% and multifocal clonic (12%). Hypoxic ischemic encephalopathy (HIE) was the commonest etiology (25.34%) then sepsis (24%), hypocalcaemia (14.67%), pyogenic meningitis (13.33%), hypoglycemia (9.33%), Kernicetrus (8%), IVH 4% and TORCH (1.33%).The consanguinity was detected in (26.7%) of patients. A response to Phenobarbitone alone was found in (42.1%) and to a combination of both phenobarbitone and phenytoin in (19.1%). The case fatality was (8%), (50%) of them were due to IVH.Conclusions: Neonatal seizures occurred mainly in full term neonates with male sex preponderance with the majority reported in their first 72 hours of life and the tonic seizures were the commonest pattern. Hypoxic ischemic encephalopathy is the main etiologic factor of neonatal seizures followed by sepsis. Intraventricular hemorrhage occurs mainly in preterm infants and it was a major cause of death.